Alterations of the Monoaminergic Systems in the Rat Brain by Sustained Administration of Carisbamate and Lamotrigine - Shim, Stacey (Université d'Ottawa / University of Ottawa, 2012)
Carisbamate (CRS) and lamotrigine (LTG) are anticonvulsants which act mainly on neuronal voltage-gated sodium channels, that have been shown to have antidepressant-like effects in animal models of depression. In vivo electrophysiological recordings were carried out following 2 and 14 days of CRS or LTG administration. Overall firing activity in the dorsal raphe, locus coeruleus and ventral tegmental area were decreased with CRS. Similarly, a decrease in the dorsal raphe was also observed with LTG. Despite these presynaptic decreases in firing activity, both anticonvulsants exhibited significant enhancement of serotonergic transmission in the hippocampus as demonstrated by increased tonic activation of postsynaptic 5-HT1A receptors. This may be attributed to the observed desensitization of the terminal 5-HT1B autoreceptors. This study suggests that the enhanced serotonergic effect may be associated with an antiglutamatergic effect, and may contribute to the antidepressant-like effect of CRS in the forced swim test and the antidepressant properties of LTG.
Keywords: anticonvulsants; in vivo electrophysiology; major depressive disorder